2017
DOI: 10.1063/1.4973502
|View full text |Cite
|
Sign up to set email alerts
|

The effects of near-bottom stratification on internal wave induced instabilities in the boundary layer

Abstract: Large amplitude internal waves in naturally occurring stratified fluids induce currents throughout the water column and hence have the potential to drive instability, and turbulent transition within, and hence material exchange across the bottom boundary layer. In the presence of broad, small amplitude topography, waves of depression have been shown to induce a vortex roll-up instability that has the potential for cross-bottom boundary layer transport through the generation of coherent vortices. At the same ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Past laboratory and numerical studies of NLIW‐BBL interaction (Boegman & Stastna, 2019, and references therein) have almost exclusively been initialized with zero or weak near‐bed stratification (Harnanan et al, 2017, is a notable exception, though their boundary‐layer rollup dynamic differs significantly from our observations). The vortex shedding, which occurs in these simulations, has thus been effectively unconstrained until the main thermocline.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Past laboratory and numerical studies of NLIW‐BBL interaction (Boegman & Stastna, 2019, and references therein) have almost exclusively been initialized with zero or weak near‐bed stratification (Harnanan et al, 2017, is a notable exception, though their boundary‐layer rollup dynamic differs significantly from our observations). The vortex shedding, which occurs in these simulations, has thus been effectively unconstrained until the main thermocline.…”
Section: Discussionmentioning
confidence: 45%
“…Beyond mobilization of bed load, Bogucki et al (1997) observed the potential for NLIWs to eject sediments high in the water column, and Bogucki and Redekopp (1999) subsequently proposed that this was due to a global instability (GI) mechanism. This GI mechanism has motivated nearly two decades of laboratory (Aghsaee & Boegman, 2015; Carr et al, 2008) and numerical (Aghsaee et al, 2012; Diamessis & Redekopp, 2006; Stastna & Lamb, 2002) studies and, more recently, studies into other novel NLIW‐induced instabilities (Harnanan et al, 2015, 2017; Olsthoorn & Stastna, 2014; Soontiens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Harnanan et al. 2017). Temporal discretization was accomplished by a third-order multistep method with adaptive time step.…”
Section: Methodsmentioning
confidence: 99%
“…This can be contrasted with the more commonly studied situation of cross-BBL transport, in which an adjustment occurs only at depth (Boegman & Stastna 2019) or at shear layers (Xu, Stastna & Deepwell 2019). The only possible exception is the case of ‘local hydraulics’ observed by Harnanan, Stastna & Soontiens (2017) for instabilities below an ISW of elevation within a secondary, near-bottom stratified layer. However, even for this case the wave-induced flow remains consistent along the topography.…”
Section: Introductionmentioning
confidence: 99%